2010
DOI: 10.3945/jn.109.110080
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Dependent Phosphate Uptake in the Jejunum Is Post-Transcriptionally Regulated in Pigs Fed a Low-Phosphorus Diet and Is Independent of Dietary Calcium Concentration

Abstract: In rodents, severe dietary P restriction increases active phosphate absorption by the intestine. However, it remains unknown if moderate dietary P restriction has a similar effect. Weanling pigs (n = 32; body weight 7.4 +/- 0.55 kg) were used in a 2 x 2 factorial design and fed dietary available P (aP) concentrations of 0.23 or 0.40% and Ca concentrations of 0.58 or 1.00% for 14 d. Diets were formulated on an aP basis instead of a total P basis, because pigs are unable to absorb phytate-P present in corn and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 30 publications
4
31
1
Order By: Relevance
“…However, the NC diet did not result in a higher NaPiIIb mRNA expression in this study. This is also in agreement with Saddoris et al (2010). Previously uncharacterized species differences in the regulation of NaPiIIb expression during low dietary P may exist, and this may be responsible for the lack of a change in the expression of NaPiIIb in the pigs on the NC diet.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, the NC diet did not result in a higher NaPiIIb mRNA expression in this study. This is also in agreement with Saddoris et al (2010). Previously uncharacterized species differences in the regulation of NaPiIIb expression during low dietary P may exist, and this may be responsible for the lack of a change in the expression of NaPiIIb in the pigs on the NC diet.…”
Section: Discussionsupporting
confidence: 78%
“…Previously uncharacterized species differences in the regulation of NaPiIIb expression during low dietary P may exist, and this may be responsible for the lack of a change in the expression of NaPiIIb in the pigs on the NC diet. As Saddoris et al (2010) reported, the increased NaPiIIb protein abundance in the brush border membranes in pigs fed low P diet was not accompanied by an increased NaPiIIb mRNA expression. Further work is needed to determine if enzymes could influence NaPiIIb protein abundance, especially since there was no enzyme effect on NaPiIIb mRNA expression.…”
Section: Discussionsupporting
confidence: 60%
“…Weaner pigs subjected to moderate dietary P restrictions can adapt by increasing absorption efficiency of P through stimulation of P uptake in the small intestine, however increases in absorption efficiency are not enough to maintain performance to that of pigs fed adequate P diets (Saddoris et al, 2010). Thus, the observed decrease in ADG and ADFI from 10 to 50 kg BW when fed a low-P diet was not surprising.…”
Section: Discussionmentioning
confidence: 89%
“…Using in situ loops of intestine [106], brush border membrane vesicles [106,108], and Ussing chambers [113] investigators have shown that dietary phosphate restriction can increase phosphate transport efficiency, e.g. in pig jejunum, phosphate transport is 90% higher in animals fed a 0.25% phosphorus diet compared to a 0.4% phosphorus diet.…”
Section: The Major Physiologic Regulator Of Intestinal Phosphate Absomentioning
confidence: 99%